Study of morbidity and mortality profile among low birth weight neonates in sick newborn care unit of a rural medical college and hospital. - Dr. Sudipta Bandyopadhyay; Dr. Abhay Charan Pal; Dr. Snehansu Chakraborti (Pediatric Review: International Journal of Pediatric Research, 2020)
Introduction: Low birth weight is one of the major health problems in children both in developed and developing countries. Birth asphyxia, neonatal sepsis, hypothermia, hypoglycemia, hyperbilirubinemia, hypocalcemia, MAS, NEC, polycythemia, IVH, meningitis, apnea, BPD, etc are the major risk factors for LBW babies morbidity and mortality. This study was conducted in a tertiary care center to find out morbidity and mortality profiles among low birth weight neonates and short-term neurodevelopmental outcome. A cross-sectional observational study. 404 low birth weight babies admitted from 1st June 2016 to 31st May 2017.Methods: Both clinical and laboratory data of all the patients were retrieved, compiled, and analyzed.Results: Out of 404 LBW 38 (9.4%) were ELBW,134 (33.2%) were VLBW and rest 232 (57.4%) were between 1500-<2500gm weight, 88 (21.8%) were preterm and IUGR, 219 (54.2%) were male and rest 185 (45.8%) were female. Major cause of morbidity includes hypoglycemia (17.6%), RDS (13.1%), HIE (29.5%), NEC (5.7%), Sepsis (47.8%), hyperbilirubinemia (31.9%), PDA (2.5%), Apnea (5.9%), IVH (1.25%), congenital anomalies (5.9%) etc.Conclusion: In the present series the mortality rate was (23.5%) was high. Sepsis, RDS, Birth Asphyxia, and Apnea were the main causes of morbidity and mortality among low birth weight babies. Proper asepsis, judicious use of antibiotics, timely intervention like CPAP, etc reduce the mortality. Proper counseling while discharge regarding feeding, warmth care, asepsis, danger sign and need for follow up plays a pivotal role in the neurodevelopmental outcome.